Metal Complexes as Antimicrobial, Antiviral and Antiparasitic Agents - Makuve, Nyasha; Makuve, Rutendo (British Journal of Healthcare and Medical Research, 2025)
Metal complexes have demonstrated multifaceted utility, serving as potent antimicrobial, antiviral and antiparasitic agents due to their diverse properties and mechanisms of action against drug-resistant pathogens. Cobalt (III) complexes to copper (II) compounds have showcased remarkable efficacy against a variety of microbial adversaries. They exhibit broad-spectrum activity, targeting viruses, bacteria, fungi, and protozoa with equal fervour. Notably, cobalt (III) complexes like the CTC series have shown promise as antiviral agents, particularly in inhibiting the replication of the herpes simplex virus and other viral strains. Similarly, copper (II) complexes have displayed potent antiparasitic properties, effectively combating parasites such as Trypanosoma cruzi, the causative agent of Chagas disease. As the threat of antimicrobial resistance looms large, the exploration of metal complexes offers a ray of hope in the quest for effective treatments. This review explores the unique properties of these metal complexes and their application as antimicrobial, antiviral and antiparasitic agents. Furthermore, the review discusses the proposed mechanism of action of metal complexes as they interact with drug-resistant microbes.